Evaluation of Noise Levels of Corn Mills in Ablekuma North Sub-Metro, Accra. - Ampofo, Daniel Komla (2014)
A Thesis submitted to the Department of Environmental Science, Kwame Nkrumah University Of Science And Technology, Kumasi in a partial fulfillment of the Requirements for The Degree of Master of Science in Environmental Science.